Pengaruh waktu layar terhadap praktik pemberian makan dengan regulasi diri pada perilaku makan anak - Dini Mei Rasaningrum; Sri Redatin Retno Pudjiati (University of Muhammadiyah Malang, 2021)
The development of self-regulation of eating is strongly influenced by feeding practice. In addition, a child’s screen time has an effect on children eating behavior. The aim of this study was to determine whether screen time acts as a moderator to the relationship between feeding practice and the ability to self-regulation eating in preschool age. Method samples were 95 mothers who had children aged 3-6 years. Participants were chosen using convenient sampling. Data were analyzed using linear regression and sub-groups analysis with ANOVA factorial 2x2. Findings show that screen time doesn’t a moderator of the relationship between restrictive feeding practice and self-regulation of eating. The conclusion is the restrictive feeding practice can interfere with children’s self-regulation of eating abilities. However, the effect of screen time doesn’t significantly contribute to moderating the relationship between restrictive feeding practice and children’s self-regulation of eating